Happiness of primary school teachers reviewed from the Big Five personality theory - Alifia Cahya Wicaksani; Farida Agus Setiawati (Psychological Research and Intervention, 2018)
This study aims to assess: (1) teachers’ happiness level, (2) dimensions of teachers’ personality, and (3) effect of the big five personality dimensions on the happiness of primary school teachers in Belik. The research applied a quantitative descriptive method with the ex-post facto approach. It took place at primary schools in Belik. The subject consisted of 210 primary school teachers in the District of Belik. The sample was established using the cluster random sampling technique. The data were collected through questionnaires, the big five was measured by an instrument called BFI, and PANAS-X and SWLS for data on happiness. The data were analyzed using the multiple regression at the significance level of 5%. The result of descriptive statistic analysis showed that: teacher’s happiness in Belik was high, for the big five dimensions of personality, the highest was extraversion followed by agreeableness, conscientiousness, openness, and neuroticism. The statistics quantitavely suggested that the types of personality significantly affected the teacher’s happiness. The Extraversion personality dimension gave contribution of 2.85%, agreeableness of 2.25 %, openness of 3.80% and neuroticism of 2.13% of happiness.